Sukupuolistuneet ammattinimikkeet - Engelberg, Mila (Virittäjä, 1998)
Gendered occupational terms (englanti) 1/1998 (102) Mila Engelberg (Department of General Linguistics (University of Helsinki); engelber@cc.helsinki.fi) Gendered occupational terms In the article the writer examines gendered occupational terms in Finnish (e.g. lentoemnt flight+hostess, ’air hostess, stewardess’; lakimies law+man, ’lawyer’) from the directory of occupations standardized and published by the Central Statistical Office of Finland (now Statistics Finland) in 1950, 1970 and 1990. The number of morphologically defined female occupational terms was 139, 41 and 85 in 1950, 1970 and 1990, respectively; the corresponding number of male occupational terms was 564, 183 and 426. The female and male occupational terms together account for about 5-6% of all occupational terms in each of the three directories. In the article, the writer further concludes that gendered occupational terms are nearly four times as common in male-dominated than in female-dominated occupations. Most male occupational terms are compounds with mies ’man’. Recent terms include ovimies (door+man, ’doorkeeper, doorman, porter’), luottamusmies (trust+man, ’trustee, delegate, employee representative’) and huolintamies (forwarding+man, ’forwarder’). Compounds with esimies ’superior, foreman, supervisor’ (e.g. liikenne-esimies ’traffic foreman’ and atk-esimies ’computer supervisor’) were still the most common type of male occupational terms in 1990 (n = 61), although their number had decreased since 1950. Compounds with tymies ’workman’ (e.g. varastotymies warehouse+workman, ’warehouseman’) and huoltomies ’maintenance man’ (e.g. konehuoltomies machine+maintenance man) have significantly increased since 1950. Titles with virkamies ’civil servant, official’ (e.g. museovirkamies museum+official), apumies ’handyman, assistant’ (e.g. rakennusapumies building+assistant) and etumies ’foreman’ (e.g. puutarhaetumies garden+foreman) had clearly become less frequent by 1990. Derivations with the feminine suffix -tAr (e.g. oopperalaulajatar ’opera singer’+FEMALE; rntgenhoitajatar ’x-ray nurse’+FEMALE) were common in 1950 (n = 77) but had almost disappeared by 1970. The 1990 directory lists six feminine derivatives with -kkO (e.g. meijerikk ’dairy woman/maid’; siskk ’housemaid’). Compounds with emnt ’hostess, lady of the house, housekeeper’ were ten times more common in 1990 (n = 60) than in 1950. New terms include bingoemnt (’bingo hostess’), pr-emnt (’PR hostess’), bussiemnt (’bus stewardess’) and saunaemnt (’sauna hostess’). The titles usually denote low status service occupations and appear euphemistic (cf. cleaning lady, Avon lady, lollipop lady). The writer believes that emnt and its male counterpart isnt ’master, head of the house, host’ may be undergoing the same kind of semantic change as word pairs like lord/lady and master/mistress in English: the male term retains its neutral or positive meaning while the female terms acquires a non-prestigious meaning. Compounds with nainen ’woman’ (e.g. seuranainen ’lady’s companion’, etunainen ’forewoman’ in a spinning mill) are very uncommon. If nainen was more productive in occupational terms, the complementary opposition of the pair nainen/mies and the gender-specific meaning of mies would become more salient, thus making it more difficult to maintain the apparently generic meaning of many male occupational terms.